Relationship between Latex Production and Physiology of Rubber Clone Pb 260 - Purwaningrum, Yayuk; Asbur, Yenni (International Journal of Engineering and Technology, 2018)
Dominant physiological characteristics of latex in Latex formation are sucrose content, inorganic phosphate, and thiol levels. Relationship between latex physiology character and factors influencing production of latex was examined in 10 years old of clone PB 260. This research aims to study and obtain data on latex physiological characteristics which considered relate to production and find out physiological characters that have significant correlation and direct effect on rubber production. The research site is Sei Putih Farm, PT. Perkebunan Nusantara III is Regency of Deli Serdang, North Sumatra, Indonesia. Clone PB 260 with planting space 2.5 m x 5 m was used as plant material in this study. Every treatment is used 75 trees with girth 65 cm - 70 cm. Based on statistical analysis, in May, June and July, sucrose levels had positive effect on latex production, while Pi and thiol had negative relationship, except in June Pi had a positive effect. In May, latex production is influenced by sucrose, Pi, and thiol by 32.5%, June 27.5% and July 38.5%.Â